23 Heart age: intuitive communication tool or gateway to overdiagnosis? A comparison of 3 countries. (4th December 2019) - Bonner, Carissa; McKinn, Shannon; McCaffery, Kirsten; Glasziou, Paul; Doust, Jenny; Jansen, Jesse; Bell, Katy
Abstract : Objectives: Heart age calculators are increasingly popular around the world as a way to promote and communicate cardiovascular disease (CVD) risk assessment to patients/consumers. While they have intuitive appeal, the implicit assumptions behind heart age calculator algorithms have important implications for informed decision making and screening programs. This presentation compares the use of heart age in three countries to illustrate potential problems for disease mongering and inadvertently expanding screening programs, and how to avoid these problems. Methods: Analysis of the use of heart age calculators to promote CVD prevention guidelines in the UK, New Zealand and Australia; including content analysis of social media reactions amongst the general public and health professional communities to demonstrate potential problems. Results: The different approaches to heart age in different countries illustrates how some design decisions and message targeting can lead to inadvertent harm, in terms of scaring/medicalising low risk people and expanding screening. A recent heart age campaign in the UK caused a backlash from GPs for encouraging cholesterol testing in young people, and led to confusion amongst the 80% of users who received older heart age results and medication recommendations. Apart from being a test for an 'important health problem', the Heart Age calculator met none of Public Health England's own assessment criteria for a potentially useful screening test. In contrast, New Zealand's heart age calculator has been aimed at GPs with clear explanations of absolute risk that reduce the chance of harm; while Australia is currently trialling a consumer-driven approach that may encourage more testing but avoids explicit medication recommendations. Conclusions: This analysis shows how some features of heart age calculators may lead to harms, and how to avoid them. We recommend that the results of heart age calculators should explicitly explain how they relate to the absolute risk of a CVD event, and avoid making recommendations for medication or tests for age groups beyond existing screening programs. When used to encourage younger people to seek unnecessary cholesterol and blood pressure tests, or recommend medication to people at low risk of a heart attack or stroke based on older heart age, they may cause more harm than benefit.